STRATEGI ADAPTIF PEMASARAN UMKM SEMBAKO DI DESA SETONO - Ilmiyatun Nafiah, Alfa; Hermawan Adinugraha, Hendri; Ade Gunawan (EKSYDA: Jurnal Studi Ekonomi Syariah, 2025)
This study aims to analyse the marketing strategies implemented by micro, small, and medium enterprises (MSMEs) in Setono Village in the face of local market changes. The main issue raised in this research is how the sembako MSMEs adjust their marketing strategies to survive and thrive amid limited resources, intense competition, and changing consumer behaviour. Using a descriptive qualitative approach through a case study method, data was obtained from interviews, observations, and documentation. The results showed that product, price, promotion, and distribution strategies are flexible and adaptive to local needs. Emphasis on social relationships and personalised service are key success factors.